Отчего и почему: [стихи] / Г. В.Сапгир - Сапгир Генрих Вениаминович (Моя любимая книжка, 2003)
Экземпляры: ф-23 (20170425) / Инвентарный номер: 51019 / Цена: 15.00 / Сис.шифр: Д / Авт.знак: С 19 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6